Política de currículo participativa em arranjo de desenvolvimento da educação (ADE): a experiência do ADE da Chapada Diamantina (BA) e a proposta da justiça curricular - Costa, Thais Almeida (2023)
Although studies that investigate educational initiatives about territorial associations have been gaining prominence, analyses in the field of curriculum are scarce. The experience of Arranjos de Desenvolvimento da Educação (ADEs) has become a way for municipalities to associate in order to find common and local solutions for public policies in education. Researchers consider Chapada Diamantina’s ADE an outstanding case of territorial cooperation due to its principles, methodology and organization modes, based on popular participation. Through the process called Sociopolitical Mobilization, which occurs in election years in the municipalities that form Arranjo da Chapada, school forums and debates with the school community and candidates for mayors and councilors are held, oriented by a curricular question: What do we desire - as school professionals, teachers, principals, coordinators and parents - in order to have a quality public education for our students? Based on the systematization of the collective demands, mayor candidates sign a term of agreement to guarantee the fulfillment of the listed proposals. After the election, their actions are monitored and assessed by a commission of representatives of schools and community regarding the qualification of educational public policies based on permanent dialogue. This research analyzes the dynamics of Sociopolitical Mobilization in the municipalities that form Chapada’s ADE as a way of building a participatory curriculum policy, based on the concept of curricular justice and its three dimensions. It has a qualitative approach which ensures that the researcher gets to know the investigated context. The other methodological paths and data collection instruments were defined in the field: document analysis, participant observation, semi-structured interviews with representatives of Chapada’s ADE and school community, secretaries of education and mayors of three municipalities participating in the initiative. The data analysis follows the principles of content analysis (BARDIN, 2016), seeking to highlight: a) the organization of Chapada’s ADE, the principles that led to its foundation, the contradictions and challenges faced; b) democratic learning and variables that interfere in the participatory process; c) which knowledge, care and demands for democratic coexistence are claimed through the generated actions. The analyzed practice reaffirms counter-hegemonic democratic alternatives - organized from the bottom to the top of society (SANTOS; AVRITZER, 2002), at the local level and from the school (FREIRE, 2001) - to struggle for social inclusion. In defense of progressive curriculum policies, based on the principles of curricular justice (PONCE, 2018) and articulating the dimensions of social justice – recognition, redistribution and representation (FRASER, 2012) - we defend that education professionals, supported by processes of conscious continuing education, are able to participate and actively intervene in the contexts of curriculum policy production (BALL; MAINARDES, 2011) as a way of claiming for their wills and fighting for their rights. We expect to contribute to the comprehension of the dynamics involved in the organization of ADEs and their regulatory process, public/private relations, arguing in favor of the standardization of a public National Education System, capable of legislating on the regime of collaboration as a State policy in order to guarantee the right to education and prioritize social participation in the decision-making processes and curricular contexts